Animations showing Lego manipulative tasks: Three potential moderators of effectiveness. (July 2015) - Castro-Alonso, Juan C.; Ayres, Paul; Paas, Fred
Abstract: Evidence suggests that transient visual information, such as animations, may be more challenging to learn than static visualizations. However, when a procedural-manipulative task is involved, our evolved embodied cognition seems to reverse this transitory challenge. Hence, for object manipulative tasks, instructional animations may be more suitable than statics. We investigated this argument further by comparing animations with statics using a Lego task shown to university students, by examining three potential moderators of effectiveness: (a) the environment of manipulation (virtual or physical), (b) the quality of visual information (focused or unfocused), and (c) the presence of hands (no hands or with hands). In Experiment 1 we found an advantage of animation over statics, and no differences among the environments. In Experiment 2, we again observed an animation advantage, a small advantage of focused static information compared to unfocused static information, and a positive effect of not showing the hands. Highlights: Learning a Lego task was similar when tested in physical and virtual environments. In both environments, animations were slightly better than static pictures. Not showing the hands solving the task was better than showing them. Focused rather than unfocused complete visual information of the task was better.